Respon Pemberian Pembenah Tanah Asam Humat Terhadap Pertumbuhan dan Produksi Jagung Manis (Zea mays L. var. Saccharata) - Trimansyah, Trimansyah; Fahri, Romi; Novianty, Lily (JURNAL AGROPLASMA, 2024)
Sweet corn (Zea mays L. var. saccharata) is a variety of corn that differs from regular corn due to its sweet taste, which is caused by its high sugar content. The productivity of sweet corn in the country is still low compared to other producing countries. The application of humic acid soil conditioner can enhance the absorption of micro and macro elements in plants. Humic acid can also improve plant growth by increasing bioavailability and nutrients through soil environment improvement around the roots. This study aims to determine the effect of humic acid soil conditioner and the appropriate dosage on the growth and yield of sweet corn. The study used a Non-Factorial Randomized Block Design (RBD) with 4 treatment levels: (H0: without humic acid soil conditioner (control), H1: 5 kg/ha, H2: 10 kg/ha, H3: 15 kg/ha). The results showed that the application of humic acid soil conditioner can increase plant height, cob diameter, and cob length of sweet corn. The best dosage of humic acid organic fertilizer for the growth and yield of sweet corn is 15 kg/ha. Keywords : sweet corn, soil conditioner, humic acid